The “Modelo Flipped Learning” en el fortalecimiento de competencias digitales para el diseño de páginas web - Tumbalobos Cabrera, Ana (2023)
The objective of the thesis was to determine the degree of influence of the "Flipped Learning Model" in the strengthening of digital skills for the design of Web pages, in students of CETPRO Rikcharisun, Ayacucho - 2021. The type of research was empirical of explanatory level and quasi-experimental design. The sample consisted of 40 participants, divided into two groups: experimental and control. For data collection, a structured observation sheet and a checklist were implemented. Reliability was determined by means of Cronbach's Alpha coefficient, the result being 0.963. The processed data was presented by means of tables, in order to proceed with the description and inference. The choice of statisticians was correlated with a "non-normal distribution" of the data, according to the Shapiro Wilk test. For the normality test, the non-parametric "Kolmogorov-Smirnov" statistic was used. The results show that there is sufficient empirical evidence (?= 0.000 < 0.050; U=6.000) indicating that the "Flipped Learning" model has a significant effect on the level of strengthening of digital skills during the design of Web pages (see table 7). In addition, it was determined that 95.0% of the students in the experimental group were at a good level of achievement, while in the control group none reached this level. Keywords. Digital competence, Web page design, model.